1999
DOI: 10.1034/j.1399-6576.1999.430804.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of intra‐articular tenoxicam, lidocaine, and pethidine for outpatient knee arthroscopy

Abstract: The combination of 20 ml lidocaine 2%, 10 mg pethidine and 20 mg tenoxicam given intra-articularly provided superior analgesia and reduced oral analgesic requirement during the first day after arthroscopy compared with lidocaine and pethidine alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The third drug we administered is tenoxicam, a NSAID which has been used in studies intraarticularly, alone or in combination with local anaesthetics [8][9][10][11][12][13]. It has been shown that i.a tenoxicam provided superior postoperative analgesia and reduced analgesic requirements compared to intravenous tenoxicam indicating a peripheral analgesic effect [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…The third drug we administered is tenoxicam, a NSAID which has been used in studies intraarticularly, alone or in combination with local anaesthetics [8][9][10][11][12][13]. It has been shown that i.a tenoxicam provided superior postoperative analgesia and reduced analgesic requirements compared to intravenous tenoxicam indicating a peripheral analgesic effect [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multimodal analgesia (or balanced analgesia) appears to constitute a rational approach to effective pain management 33, 34. Following arthroscopic procedures promising pain alleviating effects of different IA multimodal analgesic regimens have been reported 35–38. Most of the combinations have involved the use of 2–3 drug compounds selected from the above mentioned groups comprising local anesthetics, NSAIDs, and opiates.…”
Section: Common Ia Drug Therapies and Potential New Drug Targetsmentioning
confidence: 99%
“…Multiple studies have shown intraarticular injections of lidocaine to have high success rates when used as a local anesthetic for knee arthroscopy. 3,4,9,10,14,17 Based on patient comfort levels and systemic toxicity data, recommendations for bolus 20-mL intra-articular injections of lidocaine at concentrations 1% or greater for knee arthroscopy have been made. 3 Because chondrocyte loss has been implicated in the development of osteoarthritis, 6 it is important to determine whether lidocaine may also have cytotoxic effects on articular chondrocytes.…”
mentioning
confidence: 99%